Sharp Trapped Resonances by Exciting the Anti-symmetric Waveguide Mode in a Metal-Insulator-Metal Resonator - Chen, Zhao; Chen, Jianjun; Li Yu; Xiao, Jinghua (PLASMONICS, 2015)
A sharp trapped resonance is numerically predicted in a single metal-insulator-metal (MIM) resonator by exciting the anti-symmetric waveguide mode. This MIM resonator consists of a wide-gap MIM structure which is connected with a narrow-gap MIM waveguide. By introducing a small structural break in the plasmonic resonator, both of the symmetric and anti-symmetric waveguide modes are excited in the wide-gap MIM structure. By reducing the propagation loss as well as taking advantage of the different field distribution of the anti-symmetric waveguide mode, a strongly trapped resonance with a quality factor as high as about Q a parts per thousand 570 emerges in the MIM resonator. This quality factor is significantly greater than that of the MIM resonators based on the widely used symmetric waveguide mode, which has much longer propagation lengths. The utilization of the anti-symmetric mode in the MIM waveguide provides a new possibility for designing high-performance plasmonic devices.
Keywords: Anti-symmetric waveguide mode; Fano resonance; Metal-insulator-metal waveguide; Structural break; surface plasmon polaritons